INTRODUCTION TO USING ONION CULTIVATION TECHNIQUES TSS (TRUE SHALLOT SEED) IN GAMPONG LADANG VILLAGE WEST ACEH - Jekki Irawan; Maulidil Fajri; Muhammad Jalil; Iwandikasyah Putra; Dewi Andriani; Izwar; Chairul Musca; Ediyanto (RADJA PUBLIKA, 2024)
The cultivated method for some commodity of plant is one of the keys for optimum production. Shallot is one of main commodity of horticulture that has not been widely cultivated in Aceh Province especially in Gampong Ladang village West Aceh. The introduction of TSS (True Shallot Seed) is one of main idea to promote botany seed of shallot as planting material on shallot cultivation with more benefit compared of shallot bulb. The activities of public service were held in Gampong Ladang West Aceh. The methode of this activity include of: socialization, technical guidance of shallot cultivation, technic of land preparation, technic of seed germination, plantation in field, and evaluated with questioner method. The results obtained by the community are able to cultivated of shallot using TSS. The introduction and implementation of TSS on shallot cultivated is expected as information and made farmers interested to planted shallot in large area and make Gampong Ladang as centra of shallot production especially in West Aceh.